“A” for Effort: Rewarding Effortful Retrieval Attempts Improves Learning From General Knowledge Errors in Women - Abraham, Damon; McRae, Kateri; Mangels, Jennifer A. (Frontiers in Psychology, 2019)
Previous research has shown that the prospect of attaining a reward can promote task-engagement, up-regulate attention towards reward-relevant information, and facilitate enhanced encoding of new information into declarative memory. However, past research on reward-based enhancement of declarative memory has focused primarily on paradigms in which rewards are contingent upon accurate responses. Yet, findings from test-enhanced learning show that making errors can also be useful for learning if those errors represent effortful retrieval attempts and are followed by corrective feedback. Here, we used a challenging general knowledge task to examine the effects of explicitly rewarding retrieval effort, defined as a semantically-plausible answer to a question (referenced to a semantic knowledge database: www.mangelslab.org/bknorms), regardless of response accuracy. In particular, we asked whether intermittent rewards following effortful incorrect responses facilitated learning from corrective feedback as measured by incidental learning outcomes on a 24-48 hour delayed retest. Given that effort-contingent extrinsic rewards represent the intersection between an internal locus of control and competency, we compared participants in this “Effort” group to three other groups in a between-subjects design: a Luck group that framed rewards as related to participant-chosen lottery numbers (reward with internal control, not competence-based), a random Award group that framed rewards as computer generated (no control, not competence-based), and a Control group with no reward, but matched on all other task features. Both men and women in the Effort group showed increased self-reports of concentration and positive feelings following the receipt of rewards, as well as subjective effort on the retest, compared to the Control group. However, only women additionally exhibited performance benefits of effort framing on error correction. These benefits were found for both rewarded and non-rewarded trials, but only for correction of low confidence errors, suggesting that effort-contingent rewards produced task-level changes in motivation to learn less familiar information in women, rather than trial-level influences in encoding or consolidation. The Luck and Award groups did not demonstrate significant motivational or behavioral benefits for either gender. These results suggest that both reward context and gender are important factors contributing to the effectiveness of rewards as tools to enhance learning from errors.